Tata Kelola Olah Raga dengan Figur Politik dari Militer: Studi Kasus Pemerintah Indonesia dalam Konteks Sepak Bola - Sanjaya, Andika; SD, Hardi Alunaza; Buwono, Achmad Bayu Chandra; Sari, Nining Nadya Rukmana (ARISTO, 2018)
Indonesian football turns to be a â€œcolosseumâ€ of yearly political conflict among political â€œgladiatorsâ€. The government aware that according to the history, there is a closeness between football and politics. The government also aware that football can be used as a soft power to stay existed on the international stage. The problem is, the international football federation prohibit the intervention of the government and give a punishment in the shape of suspension for the violators. This paper used a case study method to explain the phenomenon. The government choose using a political figure to indirectly resolute the conflict and govern the football. The military-political figure tends to have suitable characteristics to help the government. However, the political figure has a personal political ambition. It is reasonable in Indonesia.